Exploring Student-Teachers’ Reflection on Microteaching: A Method for Achieving Continuous Professional Development - Nikmah, Alfu; Hartono, Rudi; Yuliasri, Issy; Widhiyanto, Widhiyanto (Journal of English Teaching and Learning Issues, 2025)
This paper's primary goal is to investigate perceptions of the implementation of a microteaching course using reflective teaching practice. Microteaching is a course that prepares student-teachers to become professional instructors. Reflective teaching techniques include self-reflection and reflections from teachers and peers, which lead to effective and complete evaluation. This study explores how Indonesian student-teachers perceive the implementation of microteaching and how they discover the reflection in the microteaching course. Using a qualitative approach, semi-structured interviews and focus group discussions were conducted with seven participants to gather in-depth insights into their experiences and perceptions regarding reelection in the microteaching course. The results showed that student-teachers were concerned about preparing before conducting microteaching, including searching for materials to construct a lesson plan, conducting teaching performance and evaluation, and perceiving positive arguments in the reflections given by the teacher and peers. Having strengths and weaknesses from the comments made student-teachers tend to improve their performance in the next practice. The results of this investigation have significant practical relevance for evaluating student-teachers’ teaching performance through reflection practice and for helping future teachers fulfil their requirement to be professional teachers.